LEARNING ANXIETY AND RELUCTANCE IN ENGLISH CLASS: A PHENOMENOLOGICAL STUDY OF JUNIOR HIGH SCHOOL STUDENTS' EXPERIENCES - Purnamasari, Ida; Hersulastuti; Eko Djati S., Endang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study explores the lived experiences of learning anxiety and reluctance among junior high school students in English as a Foreign Language (EFL) classroom. Employing a qualitative phenomenological approach, the research involved 12 seventh-grade students at MTs Al Kautsar. Data were collected through in-depth interviews, classroom observations, and document analysis. The findings reveal that students experience various forms of anxiety, primarily communication apprehension and fear of negative evaluation, which manifest as classroom participation reluctance. Key contributing factors include a lack of prior English learning experience, limited vocabulary mastery, and negative perceptions of English as a difficult subject. These emotional challenges significantly impact students' motivation, self-confidence, and classroom participation, with higher anxiety levels correlating with lower engagement. Despite these challenges, students employ coping strategies such as independent vocabulary study and seeking help from peers. The study underscores the critical need for supportive learning environments and pedagogical strategies that address the affective dimensions of language learning to foster greater student engagement and reduce anxiety.